2020
DOI: 10.1038/s41598-020-58598-z
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Cooling Rates and Microstructural Response during Laser Based Metal Additive Manufacturing

Abstract: Laser powder bed fusion (LpBf) is a method of additive manufacturing characterized by the rapid scanning of a high powered laser over a thin bed of metallic powder to create a single layer, which may then be built upon to form larger structures. Much of the melting, resolidification, and subsequent cooling take place at much higher rates and with much higher thermal gradients than in traditional metallurgical processes, with much of this occurring below the surface. We have used in situ high speed X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…The heating/cooling rates of the LPBF process are approximately 10 5 –10 6 K s −1 which is three orders of magnitude faster than that of traditional casting, and the thermal gradient established inside the molten pool can reach between 10 3 and 10 4 K mm −1 . To tackle such demanding scientific challenges, research teams across the globe developed different types of additive manufacturing simulators [ 13 , 26 , 97 ] combined with high-speed X-ray imaging and diffraction facilities at Advanced Photon Source (APS) [ 151 ], Diamond Light Source [ 26 , 58 , 152 ], European Synchrotron Radiation Facility [ 153 ], Stanford Light Source [ 13 , 154 , 155 ], and Swiss Light Source [ 42 ], to probe and elucidate the molten pool dynamics during LPBF.…”
Section: The Future? In Situ Imaging For Ultra-fast Solidification Processing Additive Manufacturingmentioning
confidence: 99%
See 2 more Smart Citations
“…The heating/cooling rates of the LPBF process are approximately 10 5 –10 6 K s −1 which is three orders of magnitude faster than that of traditional casting, and the thermal gradient established inside the molten pool can reach between 10 3 and 10 4 K mm −1 . To tackle such demanding scientific challenges, research teams across the globe developed different types of additive manufacturing simulators [ 13 , 26 , 97 ] combined with high-speed X-ray imaging and diffraction facilities at Advanced Photon Source (APS) [ 151 ], Diamond Light Source [ 26 , 58 , 152 ], European Synchrotron Radiation Facility [ 153 ], Stanford Light Source [ 13 , 154 , 155 ], and Swiss Light Source [ 42 ], to probe and elucidate the molten pool dynamics during LPBF.…”
Section: The Future? In Situ Imaging For Ultra-fast Solidification Processing Additive Manufacturingmentioning
confidence: 99%
“…In situ and operando X-ray diffraction or X-ray imaging in the reciprocal spacing has been used to capture the dynamic phase transformation, extract the subsurface cooling rates, and evolution of strains during LPBF of Ti-6Al-4V [ 42 , 155 , 156 ]. Cang et al [ 156 ] studied the phase transformation during a single spot LPBF of Ti-6Al-4V, showing the evolution powder underwent melting, solidification (with a cooling rate of 1 × 10 5 K s −1 ), and reported that β → α’ solid-state phase transformation is diffusionless and has a transformation rate above 10 4 μm s −1 .…”
Section: The Future? In Situ Imaging For Ultra-fast Solidification Processing Additive Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions lead to a microstructure that results in exceptional mechanical properties [2][3][4]. Many researchers have reported that the solidification microstructure obtained by LPBF was produced using cooling ranges from 10 4 K/s to 10 6 K/s and temperature gradients from 10 5 K/s to 10 7 K/s [5][6][7]. Rapid solidification is desired to design the LPBF process parameters to obtain a precise microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM) is a process in which a part or machine element is constructed from a threedimensional model with the help of CAD-CAM software, by adding successive layers. [1][2][3][4][5][6]. Although these technologies are constantly evolving [7], there is still a limited state of the art on the effects that these materials can have under working conditions, especially corrosion.…”
Section: Introductionmentioning
confidence: 99%